Brief telephone counselling is effective for caregivers who do not experience any major life events - Caregiver-related outcomes of the German day-care study - Behrndt, Elisa-Marie; Straubmeier, Melanie; Seidl, Hildegard; Vetter, Chiara; Luttenberger, Katharina; Grässel, Elmar (BMC Health Services Research, 2019)
Background: To date, there has been a dearth of scientifically tested, established intervention concepts focussed on supporting informal caregivers and embedded in routine health care structures. The aim of this study was to assess effects of a brief telephone intervention for caregivers of persons with cognitive impairment (PCIs) on caregivers' depressiveness and subjective burden. Methods: A two-arm cluster-randomised controlled intervention study was carried out at 32 German day-care centres. During the six-month intervention period, informal caregivers in the intervention group (n = 205) received counselling in three phone calls focussed on stress reduction, development of self-management strategies, and how to deal with challenging behaviours. Both the control group (n = 154) and the intervention group were free to take part in any support programmes offered by the German Health Care System (TAU). Caregivers' subjective burden and depressiveness were measured with the Burden Scale for Family Caregivers - short version (BSFC-s) and the WHO-5 Well-Being Index (WHO-5). Outcomes were assessed by means of computer-assisted telephone interviews (CATIs) at baseline and at the end of the six-month intervention phase. Multiple regression analyses were used to show the influence of group allocation. Results: After the intervention phase, group allocation was not found to significantly predict caregivers' subjective burden or depressiveness. The baseline scores (p < 0.001) were the only significant predictors of change in both outcomes. However, sensitivity analyses for caregivers who did not experience any events that they felt were major (in a negative or positive sense) during the six months (n = 271) showed that group allocation (p < 0.05) was a significant predictor of positive change in both outcomes (BSFC-s: Δ-1.3, [- 2.4, - 0.3], Cohen's d = 0.27; WHO-5: Δ1.5, [0.4, 2.7], Cohen's d = 0.26). Effect sizes were highest in the subgroup of caregivers of people with mild dementia (BSFC-s: Cohen's d = 0.43; WHO-5: Cohen's d = 0.42). Conclusions: A "low-dose" psychoeducative telephone intervention designed to empower caregivers is effective, especially in an early stage, if the overlap between the effect of the intervention and the effect of events that are experienced as major events in the caregiver's life is considered. Trial registration: Identifier: ISRCTN16412551 (Registration date: 30 July 2014, registered retrospectively).
CRIS-Team Scopus Importer:2019-05-09
Keywords: Day-care; Dementia; MCI; Informal caregivers; Telephone intervention